Development and evaluation of virtual assistant to assist elderly caregivers - Pardini, Rafael Macera; Pissolato, Tarsis de Oliveira; Ribeiro, Rita de Cássia Helú Mendonça; Bianchin, Maysa Alahmar; Rondina, João Marcelo (Seven Editora, 2024)
The increase in longevity in Brazil brings new challenges to the care of the elderly, with the caregiver of the elderly assuming, often without support or training, the responsibility of providing care to these demands. Technology supported by artificial intelligence can be used to guide and assist caregivers. In this field, virtual assistants are software with the ability to converse with human beings and have features and functionalities that can be used for this purpose. The article deals with the development and evaluation of a virtual assistant to assist caregivers of the elderly. This usage proves to be reliable, easy to use, and has a consistent knowledge base. DOI:https://doi.org/10.56238/sevened2023.007-082